Ultraviolet and magnetic perspectives at Reiner Gamma and the implications for solar wind weathering - Waller, C. D.; Cahill, J. T. S.; Retherford, K. D.; Hendrix, A. R.; Allen, R. C.; Vines, S. K.; Meyer, H. M.; Wirth-Singh, A. A. (Frontiers in Astronomy and Space Sciences, 2022)
With the wealth of missions selected to visit the lunar surface in the decade ahead, preparatory investigations into surface conditions are underway to explore potential challenges and science returns during these missions. One such mission, Lunar Vertex, is slated to explore a much-anticipated region–the lunar swirl and magnetic anomaly known as Reiner Gamma. Lunar swirls are unique natural laboratories for exploring solar wind interactions with partially magnetized rocky bodies, and possess many mysterious characteristics that have not yet been observed on any other body in the solar system. This work aims to combine current magnetic mapping of Reiner Gamma with ultraviolet wavelength datasets, towards further understanding the sensitivities of ultraviolet measurements in regions that may be at least partially magnetically shielded from solar wind weathering and magnetospheric plasma populations. Observations and models herein are collected and derived from orbital sources and will be used for comparison to future orbital and surface observations of Reiner Gamma by Lunar Vertex.